Editorial: It takes all of us to enforce the law (First Peoples Child & Family Review, 2019)
January 26, 2016, was a historic day. Nine years after the Caring Society and Asssembly of First Nations filed the case, the Canadian Human Rights Tribunal issued a landmark ruling that found Canada guilty of racial discrimination against First Nations children. Featuring interviews with the Caring Society's pro bono legal team, this short film explores the history and significance of the case through a legal lens. Thoughtful and engaging, the film is a must watch for legal professionals, educators, activists, and young people alike.